2010
DOI: 10.1186/1471-2369-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different intravenous iron preparations on lymphocyte intracellular reactive oxygen species generation and subpopulation survival

Abstract: Background: Infections in hemodialysis (HD) patients lead to high morbidity and mortality rates and are associated with early cardiovascular mortality, possibly related to chronic inflammation. Intravenous (IV) iron is widely administered to HD patients and has been associated with increased oxidative stress and dysfunctional cellular immunity. The purpose of this study was to examine the effect of three commercially available IV iron preparations on intracellular reactive oxygen species generation and lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…[61][62][63] Not surprisingly, IVI formulations have been shown to induce oxidative stress, inflammation and cellular toxicity, pro-oxidant cell signaling, tissue inflammation, cellular iron deposition, and cytotoxicity in cell culture models, animal models, and acutely in human participants [63][64][65][66][67] with more labile compounds inducing more toxicity than those with larger carbohydrate shells. 68,69 IVI has also been associated with immune dysfunction, augmentation of bacterial growth, and increased Gram-positive bacteria growth in vitro. 67,[69][70][71] Taken collectively, these studies underscore the need for comprehensive clinical and translational investigations to evaluate the effect of differences in formulation, pharmacokinetic, and pharmacodynamic characteristics and to determine whether repeated induction of oxidative stress from IVI has long-term sequelae.…”
Section: In Vitro Safety Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[61][62][63] Not surprisingly, IVI formulations have been shown to induce oxidative stress, inflammation and cellular toxicity, pro-oxidant cell signaling, tissue inflammation, cellular iron deposition, and cytotoxicity in cell culture models, animal models, and acutely in human participants [63][64][65][66][67] with more labile compounds inducing more toxicity than those with larger carbohydrate shells. 68,69 IVI has also been associated with immune dysfunction, augmentation of bacterial growth, and increased Gram-positive bacteria growth in vitro. 67,[69][70][71] Taken collectively, these studies underscore the need for comprehensive clinical and translational investigations to evaluate the effect of differences in formulation, pharmacokinetic, and pharmacodynamic characteristics and to determine whether repeated induction of oxidative stress from IVI has long-term sequelae.…”
Section: In Vitro Safety Signalsmentioning
confidence: 99%
“…68,69 IVI has also been associated with immune dysfunction, augmentation of bacterial growth, and increased Gram-positive bacteria growth in vitro. 67,[69][70][71] Taken collectively, these studies underscore the need for comprehensive clinical and translational investigations to evaluate the effect of differences in formulation, pharmacokinetic, and pharmacodynamic characteristics and to determine whether repeated induction of oxidative stress from IVI has long-term sequelae.…”
Section: In Vitro Safety Signalsmentioning
confidence: 99%
“…55 High doses of IV iron products also have been shown to impair PMN's phagocytic and bactericidal capacities. [56][57][58][59] Finally, iron preparations decrease whereas ESAs, which reduce iron stores, enhance the response to hepatitis B vaccination, 60 and iron overload increases the risk and severity of infections 61,62 by facilitating microbial growth and virulence.…”
Section: Contribution Of Iron Overload To Systemic Inflammation and Imentioning
confidence: 99%
“…In terms of peripheral blood leukocytes, therapeutic concentrations of iron in media diminished CD4+ lymphocyte survival through the intracellular oxidative stress caused by iron, which leads to apoptosis [17] . Deicher et al [18] demonstrated that high-dose parenteral iron impaired the intracellular killing of S. aureus by PMNLs.…”
Section: Host Factorsmentioning
confidence: 99%